Sports media, marketing, and management : breakthroughs in research and practice (IGI Global, 2018)
"This book is a comprehensive reference source for the latest scholarly material on the effectiveness of current methodologies and theories in an effort to improve promotional activities, management, and the organization of all aspects of the sports industry. Highlighting a range of pertinent topics such as brand management, social media, and sports tourism marketing"- Resumé vydavatel
Keywords: sportovní marketing; sportovní management; masmédia; sociální média; komunikace (sdělování); sport; sports marketing; sports management; mass media; social media; human communication; elektronické knihy; sborníky; electronic books; papers of several authors